2022
DOI: 10.1093/jamia/ocac064
|View full text |Cite
|
Sign up to set email alerts
|

ICU Cockpit: a platform for collecting multimodal waveform data, AI-based computational disease modeling and real-time decision support in the intensive care unit

Abstract: ICU Cockpit: a secure, fast, and scalable platform for collecting multimodal waveform data, online and historical data visualization, and online validation of algorithms in the intensive care unit. We present a network of software services that continuously stream waveforms from ICU beds to databases and a web-based user interface. Machine learning algorithms process the data streams and send outputs to the user interface. The architecture and capabilities of the platform are described. Since 2016, the platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Data Collection For the development of the OD models, we prospectively collected blurred anonymized video data from cameras (AXIS M1065-L) directed onto the bedsides of a 12bed neurocritical care unit at the University Hospital Zurich. The blurred video streams have a resolution of 640×400 pixels at 25 frames per second, collected by a dedicated research IT infrastructure [16]. The video data streams are blurred using a software solution for video stream conversion (FFmpeg, https://ffmpeg.org/) with a box blur filter (boxblur=6:1).…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…Data Collection For the development of the OD models, we prospectively collected blurred anonymized video data from cameras (AXIS M1065-L) directed onto the bedsides of a 12bed neurocritical care unit at the University Hospital Zurich. The blurred video streams have a resolution of 640×400 pixels at 25 frames per second, collected by a dedicated research IT infrastructure [16]. The video data streams are blurred using a software solution for video stream conversion (FFmpeg, https://ffmpeg.org/) with a box blur filter (boxblur=6:1).…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The training pipeline of the dynamic model selected C-reactive protein, Creatine kinase, Creatinine, Interleukin-6, Leukocytes, Lymphocytes ratio, Middle corpuscular volume, Serum osmolality, and Neutrophils ratio. In the ROC analysis, the final voting model showed an AUC of 0.747 ± 0.094, while the dynamic and static models had an AUC of 0.729 ± 0.083 and 0.679 + 0.131, respectively 35 .…”
Section: Methodsmentioning
confidence: 96%
“…Survey: 95 clinicians from the N-ICU participated in the online survey at the start of the design process (the response rate was high at 88.79%). To set the stage, clinicians received a video-based online instruction explaining the general purpose of the DCIP and how the system will be integrated as a plug-and-play application into the already existing ICU cockpit dashboard 35 . Participants were then presented with a patient scenario depicting an aSAH patient with ambiguous symptoms of an upcoming DCI, followed by scenario-based questions about (Q1) which actions they would take to assess the risk of DCI in the described patient without the assistance of the DCIP; (Q2) actions they would take to assess the risk of a DCI in this patient with the assistance of the DCIP; and (Q3) which factors would help them establish trust in the DCIP.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of different tree ensembles showed that Extremely Randomized Trees 26 performed best in the dataset. In the ROC analysis, the final voting model showed an AUC of 0.747 + 0.094, while the dynamic and static models had an AUC of 0.729 + 0.083 and 0.679 + 0.131, respectively 27 .…”
Section: System Descriptionmentioning
confidence: 97%